تأثير بعض الأوساط الزراعيّة على نموّ وتطوّر بادرات الخرنوب Ceratonia siliqua L. في أوعية الميني ريزوترونات - أمين, طلال; محفوض, حافظ; ناصر, سامر (Latakia University Journal -Biological Sciences Series, 2018)
This study aimed to know the effect of some agricultural substrates on the growth of seedlings carob to obtain Exceled seedlings in its shoot and root system. Where used Minirhizotron containers with three agricultural substrates : a. Altorf (T): b. Nursery soil (S): c. mixture of Altorf and Nursery soil (TS) by (1: 1). and studied several quantities indicators of growth and development of the total shoot and root system of the seedlings for a period of three months. For a radical system, results indicated a high significant superiority in the in the Altorf values for the main root of the overall growth rate such as length (cm) and the speed of growth (cm/3days) to soil substrate and insignificant state to mixture substrate. For the secondary roots (total number, total length/cm) Torf has a high significant superiority upon the other treatments. And a significant state has dominated for Altorf substrate to soil substrate in all indicators related to the shoot system such as average diameter and average height and average number of phalanges stem and leaves, and ending with the dry weight of shoots. Altorf continued in its clear positive effect when mixed it with the nursery substrate and the mixture substrate exceed on nursery substrate with varying degrees of insignificant in all previous indicators. Results for the study of periodic growth curves for the main root and main stem of the three treatments indicated the presence of a great similarity in the overall appearance of these curves and the phenomenon was observed in contrast growth Antagonism clearly between the totals shoot and root with any end to the growth of main root accompanied by a junior at the end of the main stem growth and vice versa. هدفت الدراسة لمعرفة تأثير بعض الأوساط الزراعيّة على نموّ بادرات الخرنوب للحصول على غراس متميّزة في تطوّر مجموعها الهوائي والجذري. حيث استخدمت أوعية الميني ريزوترونات معبأة بثلاثة أوساط زراعية هي: أ.التورف (T): ب. تربة المشتل (S): جـ. خليط من التورف وتربة المشتل (TS) بنسبة (1:1). ودرست عدة مؤشرات كميّة خاصة بنمو وتطور المجموع الخضري والجذري للبادرات ولمدة ثلاثة أشهر. بالنسبة للجهاز الجذري, أشارت النتائج إلى تفوق معنوي عالٍ في قيم وسط التورف الخاصة بمعدل نمو الجذر الرئيسي كالطول الكلي (سم) وسرعة النمو (سم/ 3 أيام) على وسط التربة وبدلالة غير معنوية على وسط الخليط وبخصوص الجذور الثانوية ( العدد الكلي, الطول الكلي/سم) فقد تفوق التورف بمعنوية عالية جداً على المعاملتين الباقيتين. و سادت حالة التفوق المعنوي لوسط التورف على وسط التربة بخصوص كافة المؤشرات المتعلقة بالمجموع الخضري كمتوسط القطر ومتوسط الطول ومتوسط عدد سلاميات الساق والأوراق وانتهاءاً بالوزن الجاف للمجموع الخضري. استمر التورف في تأثيره الإيجابي الواضح عند خلطه مع وسط تربة المشتل وليتفوق وسط الخليط بدرجات مختلفة من المعنوية وفي كافة المؤشرات السابقة على وسط التربة. أظهرت النتائج الخاصة بدراسة منحنيات النمو الدوري للجذر الرئيسي والساق الرئيسية لبادرات المعاملات الثلاث على وجود تشابه كبير في المظهر العام لهذه المنحنيات كما تمّ ملاحظة ظاهرة التضاد في النمو Antagonism بين المجموعين الخضري والجذري, فمع أيّ نهاية عظمى لنمو الجذر الرئيسي يرافقها نهاية صغرى في نموّ الساق الرئيسة والعكس بالعكس .